(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The density of bio-oil is 770–920 kg/m3, the heat of combustion is 43000–45500 kJ/kg. Bio-oil contains approximately 84–86% carbon, 10–14% hydrogen and 1–3% sulfur, oxygen and nitrogen. The first 4 representatives of hydrocarbons are in a gaseous state at a temperature of 0°C and a pressure of 0.1 MPa.Methane CH4, ethane C2H6, propane C3H8, butane C4H10 are included. the amount of hydrocarbons is limited, because they stick to the parts at high temperatures and form alloys in the composition of bio-oil products, it is found in a very small amount, mainly in the form of tar-asphalt substances (0.3 %).